Quantum Learning Model Assisted with Video Have an Effect to Science Learning Outcomes - Kusmayani, Made Era; Dibia, I Ketut; Sukmana, I Wayan Ilia Yuda (Universitas Pendidikan Ganesha, 2020)
The learning model applied tends to still be centered on the teacher (teacher centered) so this study aims to determine the effect of a quantum learning model assisted by video media on the learning outcomes of fourth grade elementary school science students. This type of research is quasi-experimental research design with Non-equivalent Post-Test Control Group Design. The population in this study were 133 students. Sampling was taken by random sampling. The method used in data collection is an objective test. Data analysis through descriptive and inferential statistical analysis stages. Based on the results of t-test calculations show (t = 5.54 sig = 0.00). This shows that there are differences in science learning outcomes between groups of students who are taught with a quantum learning model assisted by video media and groups of students who are not taught a quantum learning model assisted by video media to fourth grade elementary school students. Thus, the use of a quantum learning model assisted by video media will affect the learning outcomes of science students in grade IV elementary school.